Marhabanan Structure Study in Cikatapis Village, Keong Village, Rangkasbitung District, Lebak, Banten - Aditya, Dimas; Hadiyatno, Hadiyatno; Septian, Dadang Dwi; Rizal, Syamsul (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
Banten is a province that has arts in the same family as West Java. Bsnten people have one type of Islamic art that focuses more on sound. The Islamic art found in Banten is Marhabanan art, an Islamic art that will show the characteristics and identity of art among communities in other regions. This research uses qualitative research methods with a Case Study approach which is used to investigate and understand an event or problem that occurs by collecting various kinds of information which are then processed to get a solution so that the problem that occurs can be resolved. This research will also describe the results of the research in a narrative manner, and the data collection uses 3 stages, namely: (1) observation, (2) interview and (3) documentation. From the results of the study it can be concluded that Marhabanan has important structures contained in it, namely: (1) Outer Structure and (2) Inner Structure, as well as knowing the functions in reading Marhabanan. in this case, the Marhabanan art in Banten can be categorized as one type of Islamic art and performing arts owned by the people of Banten and makes it a distinctive Islamic art owned by the people of Banten.